Magnetic and electrical properties of Z-type hexaferrites sintered in different atmospheres. (May 2015) - Zhang, Xiaozhi; Yue, Zhenxing; Meng, Siqin; Peng, Bin; Yuan, Lixin
Graphical abstract: Oxygen atmosphere played an important role in inhibiting electrons hopping between Fe 2+ and Fe 3+ and reducing both of magnetic and dielectric losses of Ba3 Co2 Fe24 O41, which is favorable in view of antenna substrate applications. Highlights: Co2 Z-type hexaferrites were sintered in different atmospheres. The losses of the sample sintered in O2 were reduced effectively without additive. A 3RC equivalent circuit model was put forward in the impedance analysis. Abstract: Co2 Z-type hexaferrites with stoichiometric composition of Ba3 Co2 Fe24 O41 were fabricated by using a conventional solid–state reaction method. The influence of sintering atmosphere, namely air, O2 and N2, on magnetic and electrical properties of the hexaferrites was systematically investigated. This work reveals that O2 played an important role in inhibiting the formation of Fe 2+ and thus reducing magnetic and dielectric losses. The Co2 Z specimen sintered at 1300 °C in O2 atmosphere showed promising magneto-dielectric properties. Specifically, the magnetic and dielectric losses were less than 0.05 and 0.005 in the frequency range of 30–300 MHz, respectively. Impedance spectra were performed to reveal the underlying mechanisms for the different electrical properties of the Co2 Z ceramics sintered in different atmospheres.